Zinc oxide nanoparticles mediate bacterial toxicity in Mueller-Hinton Broth via Zn2+ - Caron, Alexander J.; Ali, Iman J.; Delgado, Michael J.; Johnson, Dustin; Reeks, John M.; Strzhemechny, Yuri M.; McGillivray, Shauna M. (Frontiers in Microbiology, 2024)
As antibiotic resistance increases and antibiotic development dwindles, new antimicrobial agents are needed. Recent advances in nanoscale engineering have increased interest in metal oxide nanoparticles, particularly zinc oxide nanoparticles, as antimicrobial agents. Zinc oxide nanoparticles are promising due to their broad-spectrum antibacterial activity and low production cost. Despite many studies demonstrating the effectiveness of zinc oxide nanoparticles, the antibacterial mechanism is still unknown. Previous work has implicated the role of reactive oxygen species such as hydrogen peroxide, physical damage of the cell envelope, and/or release of toxic Zn 2+ ions as possible mechanisms of action. To evaluate the role of these proposed methods, we assessed the susceptibility of S. aureus mutant strains, ΔkatA and ΔmprF, to zinc oxide nanoparticles of approximately 50 nm in size. These assays demonstrated that hydrogen peroxide and electrostatic interactions are not crucial for mediating zinc oxide nanoparticle toxicity. Instead, we found that Zn 2+ accumulates in Mueller-Hinton Broth over time and that removal of Zn 2+ through chelation reverses this toxicity. Furthermore, we found that the physical separation of zinc oxide nanoparticles and bacterial cells using a semi-permeable membrane still allows for growth inhibition. We concluded that soluble Zn 2+ is the primary mechanism by which zinc oxide nanoparticles mediate toxicity in Mueller-Hinton Broth. Future work investigating how factors such as particle morphology (e.g., size, polarity, surface defects) and media contribute to Zn 2+ dissolution could allow for the synthesis of zinc oxide nanoparticles that possess chemical and morphological properties best suited for antibacterial efficacy.